[Arkusz znaczków podziemnych o tematyce II wojny światowej] . Sheet of unofficial stamps with World War II themes - Poczta Solidarność - Samorządna Rzeczpospolita. (Poczta Solidarność)
Black and red print on white paper, without perforation. Sheet, with "Poczta Solidarność" and "Samorządna Rzeczpospolita" imprints, consists of 2 sets of 3 stamps which represent images related to the Nazi and Soviet invasion of Poland in 1939, with captions "Ribbentrop-Molotov pact" and "4th Partition of Poland". Price range: 20-50 zł per stamp.